ChatGPT dan Ancaman terhadap Kemampuan Berpikir Kritis Mahasiswa : AWK Foucault pada Podcast GCED Isola Edu ChatGPT: Ini Respon Terbaik Dunia Pendidikan - Nurul Hidayah; Laksono Hafid Firmansyah; Firstly Yusuf Ar Ridho Rochman; A.A.I Prihandari Satvikadewi (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This study aims to analyze how ChatGPT has an impact on the way students and students think critically in the academic field. This article examines this topic based on descriptive qualitative research techniques with the perspective of critical discourse analysis, Foucault's model of knowledge and power. The media used as material for analysis in this research is excerpts from the GCED ISOLAedu podcast with the podcast title "ChatGPT: This is the Best Response in the World of Education". The results of this research show that critical thinking skills can be threatened if humans as actors do not have awareness of ChatGPT technology education itself and require strategies, especially teaching staff, in creating students and students who are able to have ethics and critical thinking skills in responding to ChatGPT technology.